Feasibility Study Analysis of Mr. Yulianto's Tofu And Tempe Factory In View From Human Resources - Elma, Tiara; Febliansa, M. Rahman; Monique, Eska Prima (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to conduct an in-depth analysis of the operations of the tofu and tempe factory owned by Mr Yulianto, with a focus on the human resources (HR) aspect. The method used is a descriptive method with a qualitative approach, where data is collected through interviews, direct observation and document analysis. The main objective of this research is to evaluate the availability, quality and management of human resources that support the continuity of factory operations. The analysis results show that the factory has an adequate number of workers, but there are weaknesses related to employee skills and training. Lack of optimal HR management also affects factory operational productivity and efficiency. Research recommendations include improving training programs, improving recruitment systems, and implementing more effective performance management to increase employee competency and motivation. It is hoped that improvements in HR management can make Mr Yulianto's tofu and tempeh factory more competitive and sustainable in the future.